Rossini round trip. Un petit train de plaisir by Azio Corghi (Itinera, 2020)
The ballet Un petit train de plaisir for two pianos and percussion by Azio Corghi is based on pieces for piano contained in Gioachino Rossini’s Pechés de vieillesse, and was performed for the first time at the Rossini Opera Festival in 1992. The comparison with the Rossini texts, that Corghi puts into effect in his compositional work, seems to configure an eccentric position both with respect to the keywords of musical aesthetics that were for a long hegemonic in the second half of the twentieth century, and with respect to the ‘post-modern’ opening that also affected music from the early seventies. Processes of sound amplification and timbre differentiation articulate a sympathetic relationship with the author of the paratexts. A relationship that takes the form of an irony understood as doubling, in which what is said tends to mean something other than what appears.
Keywords: Keywords: musical rewriting, twentieth century music, hermeneutics, irony